Professores de Libras : Identidades e Práticas Pedagógicas - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This research treats of Identity and Pedagogical Practices Pounds of Teachers from the Universidade Federal do Amazonas, crowded in the Departamento Letras-Libras, in ICHL - Instituto de Ciências Humanas e Letras, covering the period 2012- 2015.The thesis aimed to: analyze the multiple and faceted identities of pounds of teachers from the Universidade Federal do Amazonas, to understand their teaching practices from the constitution of the deaf and hearing cultures; specifying: identify the profile of deaf teachers and listeners pounds discipline, of the Universidade Federal do Amazonas considering his views about the sign language as constitute of deaf culture; investigate the current language policies of teaching pounds for the interpretation of the relationship between deaf movement and identity construction of the deaf teachers and listeners pounds discipline; describe the pedagogical practices of deaf and listeners teachers in teaching discipline pounds degree courses; and correlate multiple and faceted identities of teachers with pedagogical practices developed in pounds discipline.The approach of this research is qualitative, interpretive, with hermeneutic-dialectic intention seeks to understand and explain the dynamics of social relations.The research adopted as participants the pounds teachers UFAM. They were interviewed 10 Pounds teachers UFAM. Among these, 06 are deaf and 04 are listeners. Questionnaires and interview technique were used in this research. It was used in this inquiry, semi-structured interview guide. It was opted for the individual interview, since it was possible to work with the interpretation of speeches in an attempt not only to analyze what the other said, but also interpret the subtext, the subtext, this is also analyze what is not said in the speech: silence. In this sense, the Discourse Analysis corroborated under a Foucault's perspective and served as the basis for the analysis of the data in relation to the interviews, knowing, of course, that such statements were regulated from the places where these subjects, men and women, talked since the implementation of the speeches is bypractice. The results indicate, in Pounds Teachers an interweaving of Identities and Pedagogical Practices, permeated with power and knowledge in subjects from their identity constructions, develop their pedagogical practices.
Keywords: Professores de Libras; Identidades; Práticas Pedagógicas; CIENCIAS HUMANAS: EDUCACAO